Validation of Guy’s Stone Score, RUSS, S-RESC SCORE, and S.T.O.N.E Score for Predicting Stone Free Rate in Percutaneous Nephrolithotomy in a Residency Teaching Hospital - Panelewen, Bryan P.; Arianto, Eko; Astram, Ari; Toreh, Christof; Wihono, Frendy (Universitas Sam Ratulangi, 2025)
Abstract: Kidney stones represent a significant health burden globally, with a high risk of recurrence. Percutaneous nephrolithotomy (PCNL) is the primary treatment option for kidney stones larger than 20 mm, offering superior outcomes compared to open surgery. Several scoring systems, including Guy’s Stone Score (GSS), S.T.O.N.E. Nephrolithometry Score, Resorlu Unsal Stone Score (RUSS), and Seoul Renal Stone Complexity (S-ReSC), have been developed to predict the Stone-Free Rate (SFR) following PCNL. However, the comparative effectiveness of these scoring systems remains unclear. This study aimed to evaluate and compare the predictive accuracy of GSS, S.T.O.N.E., RUSS, and S-ReSC scoring systems in determining SFR after PCNL. This was an analytical and retrospective study. Data were collected from 60 patients with kidney stones treated at Prof. Dr. R. D. Kandou Hospital Manado from January to December 2023. Patients underwent PCNL, and preoperative non-contrast CT scans and postoperative plain abdominal X-rays were used for evaluation. Statistical analyses included univariate, bivariate, and multivariate tests, as well as ROC curve analysis. The results showed that all four scoring systems were statistically significant in predicting SFR (p<0.005). The RUSS score demonstrated the highest predictive value, with an odds ratio 20 times higher than without scoring. The ROC analysis showed AUC values of 0.792 for GSS, 0.913 for RUSS, 0.694 for S-ReSC, and 0.945 for S.T.O.N.E. These findings highlight significant relationships between stone complexity scores and SFR, emphasizing their utility in surgical planning. In conclusion, each scoring system has significant predictive value for SFR following PCNL. Among them, RUSS showed the highest reliability, followed by S.T.O.N.E. and GSS. Despite differences in focus, all scores contribute to treatment planning and patient management. Further research is needed to optimize these tools and integrate them with advanced imaging and minimally invasive techniques for personalized patient care. Keywords: percutaneous nephrolithotomy; kidney stones; Stone-Free Rate; Guy’s Stone Score; S.T.O.N.E Nephrolithometry Score; Resorlu Unsal Stone Score; Seoul Renal Stone Complexity